2024
DOI: 10.1002/ksa.12038
|View full text |Cite
|
Sign up to set email alerts
|

Large variation in postoperative rehabilitation protocols following operative treatment of osteochondral lesions of the talus: A systematic review and meta‐analysis on >200 studies

Tristan M. F. Buck,
Jari Dahmen,
Igor J. R. Tak
et al.

Abstract: PurposeA treatment‐specific rehabilitation protocol and well‐defined return‐to‐play criteria guide clinical decision‐making on return to normal function, activity, sports and performance after surgical treatment for osteochondral lesion of the talus (OLT). The optimal rehabilitation protocols in the current literature remain unclear. The purpose of this study was to explore the existing literature on rehabilitation protocols from the early postoperative phase to return to sport onwards after different types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, further evidence base development in terms of supporting specific quantitative and qualitative research methods, modes and data collection timing by the surgical and rehabilitation teams anywhere along the healthcare continuum is greatly needed. Recent systematic reviews on clinical practice guidelines for postsurgical rehabilitation have shown that these most often provide limited, somewhat heterogeneous information and may not always reflect the best available evidence [1,3].…”
mentioning
confidence: 99%
“…However, further evidence base development in terms of supporting specific quantitative and qualitative research methods, modes and data collection timing by the surgical and rehabilitation teams anywhere along the healthcare continuum is greatly needed. Recent systematic reviews on clinical practice guidelines for postsurgical rehabilitation have shown that these most often provide limited, somewhat heterogeneous information and may not always reflect the best available evidence [1,3].…”
mentioning
confidence: 99%